Biomechanical Analysis and Solution Suggestions of Screw Replacement Scenarios in Femoral Neck Fracture Surgeries: Finite Element Method - Yılmaz Güvercin; Murat Yaylacı; Ayberk Dizdar; Mehmet Emin Özdemir; Sevil Ay; Ecren Uzun Yaylacı; Umitcan Karahasanoğlu; Hüseyin Uygun; Gökhan Peker (Orthopaedic Surgery)
ABSTRACT Objective Despite several surgical options, there has yet to be a consensus on the best treatment for femoral neck fracture (FNF) due to higher complication rates compared to other bone fractures. This study aims to examine the possible consequences and solution suggestions of changing screws during surgery for various reasons in FNF surgical treatment from a biomechanical perspective. Method FNF and treatment materials were analyzed biomechanically using a package program based on the finite element method (FEM). This study created a solid model with images of femur bone tomography. Dynamic hip screws (DHS), cannulated screws (CCS), and medial buttress plates (MBP) were obtained by making three‐dimensional designs. The required elements for the models were assigned, and the material properties of the elements were defined. The solutions were obtained as crack distance and deformation results after defining the boundary conditions and applying the necessary loading. Results The strain and crack distance values created by six models on the fracture line under different parameters were obtained, and the numerical results were evaluated. The DHS and CCS models produced the highest crack distance and deformation values when all screws were loose. The lowest values were obtained in the intact‐85 model when all CCS were tight. When the results are evaluated, it is seen that the MBP has a decreasing effect on the results. Mechanical evaluation of six different options used in femoral neck fractures was performed. 85 mm CCS applied to our standard model gave the best results, while the use of 80 mm CCS in the same model showed promising results compared to other models. It is understood that CCS have the best stability even in loosening models with the medial support plate. Different models are from intact‐85 mm DHS+1CS+MBP to DHS+1CS, which was worked with LSR+USR‐2, according to decreasing stability. Conclusion This study offers various biomechanical solutions to possible intraoperative problems in FNF treatment. The following results were obtained from the study data. When the CCS needs to be lengthened or replaced, it is appropriate to use the CCS with the MBP. A single anti‐rotation screw is sufficient for lag screw extensions of the DHS plate, and the MBP may be a savior procedure in surgery.